Removal of Heavy Metal Mercury (Hg) Liquid Waste through Electrolysis Method in Paya Ateuk Village, Pasie Raja District, South Aceh - Darmawan Darmawan; Susy Sriwahyuni (Universitas Teuku Umar, 2021)
Electrolysis is one of the methods used to remove heavy metal mercury (Hg). The electrolysis process is carried out on residual liquid waste from gold processing by utilizing chemical reactions through electrodes immersed in an electrolyte solution. This research method is experimental. We conducted laboratory tests to see the electrolysis process on the residual liquid waste from gold processing in a 10-liter container. We took samples from 10 different containers, 1 liter each from each tub. Sampling time was carried out in the morning, afternoon, and evening. The results showed a significant decrease in mercury (Hg) levels up to 1.30% with 12 volts of electricity for 100 minutes. In contrast, the lowest decrease occurred in the electric current of 3.3 volts within 25 minutes. We use the electrolysis method. This heavy metal removal technique can be applied and managed properly by the community and local government to minimize heavy metal pollution such as mercury in the surrounding environment due to waste from the community's traditional gold processing.